Kewenangan Penanganan Perkara Tindak Pidana Pencucian Uang oleh Anggota TNI Aktif - Jessica, Jeanny (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
Money laundering is an extra ordinary and transnational crime that can threaten the stability and integrity of a country's economy and even damage the joints of the country. This criminal act can be committed by all segments of society, but mostly are those who have more power and intelligence. The active Indonesian National Army (TNI) that is given more authority by the Law in Indonesia also has the potential to commit Money Laundering crime. Regulations regarding the legal process against active soldiers of the TNI who commit criminal acts are under the authority of military investigations, as stipulated in article 24 paragraph (2) of the 1945 Constitution of the Republic of Indonesia and Law Number 48 of 2009 concerning Judicial Power in conjunction with Law Number 31 of 1997 concerning Military Courts. Recently, if there are cases of active TNI soldiers who have committed criminal acts such as corruption and / or money laundering, considering that there is no specific legal framework yet, then to fill the loopholes, provisions in the Military Court Law are used.